Gait Training with Body Weight Support in Subacute Stroke - มูลดี พรรธิภา; โอวาทกานนท์ ปกาสิต; ชัยวัฒน์ ภครตี; แสงเรืองรอบ ศศิธร (Journal of Health Science of Thailand, 2022)
Stroke is a major public health problem. In which patients with hemiplegia are weakness in one limb, resulting in decreased ability to walk. The important goal is to be able to stand back and walk quickly. Recovery currently uses equipment and technology to assist in walking training, but there are limitations requiring a caretaker to control people for a limited time. And the price is very high Objective: To study the results of walking training using walking with body weight support in stroke rehabilitation patients. This study was a quasi-experimental research in patients with stroke for within 6 months, admitted to Saimoon Hospital, in total of 20 patients, divided into 2 groups. With lottery methods, the experimental group was trained to walk by using body weight support to support walking for 30 minutes with the physical rehabilitation program. The control group received the physical therapy rehabilitation program only 3 times a week for 4 weeks before and after the training. The walking ability was assessed by the Functional Ambulatory Category (FAC) and balance was assessed by the Berg Balance Scale (BBS). The data was analyzed using Mann-Whitney U test. The results showed that the walking ability level (FAC) and balance (BBS) increased ability after the experimental group training program better than the control group. In the experimental group, the median FAC increased from 0.50 level to 1 level and the BBS median increased from 11.50 points to 43.50 points. From the research, it can be concluded that Training for stroke patients in the rehabilitation phase using walking by body weight support combined with physical therapy programs can increase walking ability levels and balance better than the physical therapy program alone.